The North American idea a vision of a continental future - Pastor, Robert A. (Oxford University Press, 2011)
"In The North American Idea, eminent scholar and policy-maker Robert A. Pastor dissects the failure of NAFTA and argues that, to re-invigorate North America's economy, our leaders need to start with an idea based on a principle of interdependence. If one country fails, all three are harmed, and if one grows, they all benefit. Drawing on first-hand experience as a policy-maker and analyst, Pastor shows how this idea--once woven into the national consciousness of the three countries--could mobilize public support for continental solutions to problems that have confounded each nation working on its own"--